EEG band power analysis corresponding to salivary amylase activity during stressful computer gameplay - Sahroni, Alvin; Mahananto, Faizal; Zakaria, Hasballah; Setiawan, Hendra (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2022)
The cortisol and norepinephrine from human salivary can represent psychological conditions. A portable salivary amylase monitor device (sAA) has existed; however, how the sAA corresponds to the central nervous system changes is still limited to carry out. Twenty university students aged between 20 and 22 years participated in which they played a stressful computer game during the experiment. Nineteen EEG electrodes were attached to the head scalp while the relative power on the delta, theta, alpha, and beta-band was calculated. The sAA value was obtained using a portable device called Nipro Cocorometer from Japan. The sAA levels and the brain's relative band power increased. Beta waves of the brain's right hemisphere were found higher than that of the left hemisphere, especially on the right temporal (T4, p < 0.01). Then, we concluded that the beta-band power on the right hemisphere corresponds to wthe sAA changes.